2017
DOI: 10.1021/acs.jafc.7b02352
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan and Laminarin as Alternatives to Copper for Plasmopara viticola Control: Effect on Grape Amino Acid

Abstract: Copper fungicide use is limited by the European regulation; therefore, new strategies have been developed to prevent grapevine downy mildew (GDM). However, there is poor information about their effects on grape amino acid composition. This field trial aimed to evaluate the effect on grape amino acid composition of chitosan and of a mixture of laminarin and Saccharomyces extracts (LamE), applied in different strategies with copper hydroxide. The results showed that all the treatments applied to grapevines decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 36 publications
0
41
0
Order By: Relevance
“…Vitalini et al 47 Laminarin Grape Decreased free amino acid contents Garde-Cerdán et al 22 Methyl jasmonate Grape Increased His, Ser, Trp, Phe, Tyr, Asn, Met and Lys contents Garde-Cerdán et al 48…”
Section: Winementioning
confidence: 99%
See 2 more Smart Citations
“…Vitalini et al 47 Laminarin Grape Decreased free amino acid contents Garde-Cerdán et al 22 Methyl jasmonate Grape Increased His, Ser, Trp, Phe, Tyr, Asn, Met and Lys contents Garde-Cerdán et al 48…”
Section: Winementioning
confidence: 99%
“…Therefore, foliar application has been a recent technique that has provided improvements to must quality in relation to the amino acid and phenolic and volatile compound concentrations . Nevertheless, some studies have reported that the use of foliar applications can have little, or indeed negative, effects on grape berry quality …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional viticulture disposes of agrochemicals such as inorganic fertilizers and synthetical chemical pesticides to the farming management, whereas these aforesaid products are banned in organic viticulture and only organic fertilizers and a certain non-synthetic pesticides are allowed in the agricultural management [4,5]. In organic viticulture, diseases control is mainly carried out using copper or sulfur treatment, while weed management is performed by tillage or grass-cutting [4,6,7]. Due to the high ability to adapt to the environment and its hardly manageable, weeds could affect productivity by competing with the vines [8].…”
Section: Introductionmentioning
confidence: 99%
“…A significant reduction in net photosynthesis and transpiration rate began to occur in early August, when the canopies were sprayed, resulting in lower TSS at harvest and an increase in anthocyanin concentration, without affecting TA. A previous study reported that the formation of the film from natural products can also provide a protective role against pathogen attack in other crops as well as grapevines (Garde-Cerdàn et al 2017).…”
Section: Introductionmentioning
confidence: 99%